Research note: Assessing disturbance and its impact on behavior in the early-life of broiler chicks - Alexandra Jackson; Denise Landers; Joseph Purswell; Bethany Baker-Cook (Poultry Science)
Behavioral disturbance in poultry is relatively understudied; however, it plays an important role in influencing bird well-being. While disturbance to rest has been well-examined, all behaviors are susceptible to disturbance by conspecifics and merit evaluation. This study assessed behavioral disturbances in broiler chicks during the first week of life, focusing on variations in age, time-of-day, and the impact of disturbance on behavior performance. Seventy-five mixed-sex chicks were randomly placed into three pens (25 birds/pen), with three focal subjects per pen (n = 9). Behavior was continuously recorded from days 1 to 7 of age. Chick behaviors assessed include locomotive, sleeping, sitting, eating, drinking, preening, allopreening, comfort, exploratory, and play. Disturbances were recorded and analyzed for frequency by age and time of day. The likelihood of chicks resuming a behavior post-disturbance was calculated. One-way ANOVAs were conducted to assess the impact of age and time of day on disturbance frequency and behavior type on the return to behavior. The frequency of disturbances was highest on day 1 of age, with exception of day 2. Disturbances decreased on day 3 of age and then declined further on Day 6 (P < 0.01). Furthermore, disturbance to behavior occurred more during the mid-day period, afternoon, evening than the pre-dark period and morning period (P < 0.01). The type of behavior (P < 0.01) disturbed also affected the likelihood of return, with chicks more likely to resume locomotive, sitting, sleeping, drinking, eating, and preening behaviors than allopreening, exploratory, play, or comfort behaviors. Overall, chick age and time of day influenced the frequency of behavioral disturbances during the first week of life. Additionally, the type of behavior performed pre-disturbance did affect the likelihood of returning to that behavior. These findings highlight the potential impact of environmental novelty post-placement and chick diurnal activity during early-life have on disturbance frequency, and how the function of behaviors influence their return post-disturbance. Further research is needed to assess the long-term impact of disturbance on the behavior and well-being of birds.